(untitled) (Conferencea, 2022)
It is known that the surrounding environment is diverse and the sounds and smells in it are very colorful depending on the temperature. The environment and the human organism are constantly interrelated. This connection is provided through sensory organs, that is, all factors of the external environment affect the sensory organs and are received by their centers in the brain.